(untitled) (Research, Society and Development, 2021)
From the emergence of the Supplementary Pension Scheme, all federal public servants who joined before the creation of the Complementary Pension Foundation of the Federal Public Servant of the Executive Branch - Funpresp, entitled to full, can migrate, by prior and express option, irrevocable and irrevocably, to the PRC. In this scenario, there is a dilemma among statutory civil servants regarding the possibility of migrating to the PRC. The analysis of the profile of the servants and the motivation that led them not to opt for migration to the PRC can contribute to the understanding of the people management bodies of the public service with regard to the preparation of more specific training and focused on issues identified in the present study. In view of this situation, the present study aims to identify what are the justifications given by federal public servants who did not migrate to the PRC and, consequently, did not join Funpresp. As a methodology, a questionnaire was applied with the servers who were performing their activities in a Public Institution, and who had not yet opted for regime migration. From the data obtained, it was found that the main reasons for non-access to the Supplementary Pension are age, the remaining contribution time to retirement, the uncertainty as to the future value of the special benefit, the uncertainty regarding legal certainty in the future payment of the special benefit and the risk of mismanagement in the investments of the plan.